2016
DOI: 10.1111/cup.12764
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of mature adipocytic component within cutaneous smooth muscle neoplasms

Abstract: Angioleiomyoma is a benign smooth muscle tumor of the subcutis. The presence of mature adipocytes has been described in this tumor under the rubric of 'angiolipoleiomyoma' or, erroneously, 'angiomyolipoma' (these are not PEComas). Previous studies have found adipocytes in only 2-3% of angioleiomyoma. Anecdotally, the incidence appeared to be greater than this in our practice. Moreover, the presence of adipocytes has not been evaluated in pilar leiomyoma or cutaneous leiomyosarcoma. We searched the pathology ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The proportion of the fatty component within the lesion is highly variable and may be shown as an almost entirely fatty neoplasm simulating lipoma. Several pathogenetic mechanisms underlying the presence of fat cells within leiomyoma have been discussed previously [3][4][5]16]. Although the direct transformation (metaplasia or Our study demonstrated that adipocytic transdifferentiation, as shown by intracellular lipid accumulation and the enhanced expression of adipogenic markers (i.e., adiponectin, perilipin-1), can be elicited in cultured uterine leiomyoma cells by XAV939 treatment together with serum starvation and hypoxia.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The proportion of the fatty component within the lesion is highly variable and may be shown as an almost entirely fatty neoplasm simulating lipoma. Several pathogenetic mechanisms underlying the presence of fat cells within leiomyoma have been discussed previously [3][4][5]16]. Although the direct transformation (metaplasia or Our study demonstrated that adipocytic transdifferentiation, as shown by intracellular lipid accumulation and the enhanced expression of adipogenic markers (i.e., adiponectin, perilipin-1), can be elicited in cultured uterine leiomyoma cells by XAV939 treatment together with serum starvation and hypoxia.…”
Section: Discussionmentioning
confidence: 57%
“…Adipocytic transdifferentiation or metaplasia may be representative forms of such phenotypic plasticity. The phenomenon is most commonly encountered in neoplastic conditions of smooth muscle cells such as leiomyomas and angiomyomas [1][2][3]. However, the detailed mechanisms underlying adipocytic transdifferentiation remain largely unknown; however, the adipocytic differentiation of pluripotent mesenchymal cells in such lesions and the direct transformation of neoplastic smooth muscle cells are possible explanations [3][4][5].…”
mentioning
confidence: 99%